Productive piano pedagogy: towards a compositional approach to piano lessons in a South African primary school in Makhanda, Eastern Cape - Wynne, Donovan (Rhodes University, Faculty of Humanities, Department of Music and Musicology)
Despite global trends towards creative and productive musical learning, there is little available research on how to support music educators' efforts to adopt productive praxis in piano lessons in primary schools, and none situated in South Africa. This climate of pedagogical innovation makes possible a turn to play-based teaching methods emerging from the global north, which are aligned with African traditions of knowledge transmission in which agentive participation in authentic cultural processes is of greater value than evaluative judgements of ensuant products. The literature advocates the cultivation of music learning ecologies that privilege learner agency through composition, yet practical means of doing so within established conventions of instrumental music tuition in South African primary schools are not provided. This thesis investigates how such an ecology might be cultivated in a primary school in the Eastern Cape, with particular emphasis on how this can be achieved without compromising established pedagogical practises that are oriented toward the attainment of important external benchmarks of musical achievement. A design-based study was conducted in a primary school over the course of 12 months, in which nine young students composed their own music during piano lessons through collaborative activity in which they were afforded a degree of autonomy in their work as they acquired and consolidated knowledge of music through its creation. A play-based teaching intervention was devised, which was iteratively enacted, analysed, and redesigned through three research cycles. This resulted in findings that drove the development of a framework for teaching composition in this context, as well as tangible teaching materials. Results show that this adapted play-based model is an effective vehicle for fostering an agentive music learning ecology in piano lessons in an Eastern Cape primary school and suggest that it is reasonable to expect similar success in comparable school contexts. The insularity of a single school setting limited this research in terms of broader applicability, so further trialling of the proposed framework is recommended in a range of school situations in South Africa and beyond to establish transferability.
Keywords: Composition (Music); Piano pedagogy; Cultural-historical activity theory; Design-based research; Hogenes, Michel; School music